Total IN.PACT drug-coated balloon initiative reporting pooled imaging and propensity-matched cohorts - Shishehbor, Mehdi H.; Schneider, Peter A.; Zeller, Thomas; Razavi, Mahmood K.; Laird, John R.; Wang, Hong; Tieché, Christopher; Parikh, Sahil A.; Iida, Osamu; Jaff, Michael R. (Journal of Vascular Surgery, 2019)
Randomized controlled trials have shown that drug-coated balloons (DCBs) provide superior results compared with percutaneous transluminal angioplasty (PTA) for the treatment of femoropopliteal artery disease. However, these trials have generally included short lesions, few occlusions, and small sample sizes. The present study was an individual-level pooled analysis of duplex ultrasonography (DUS) core laboratory-adjudicated and clinical events committee-adjudicated IN.PACT Admiral DCB subjects across two randomized controlled trials and two single-arm prospective studies to characterize the safety and effectiveness of DCB compared with PTA. The subjects were treated with DCB (n = 926) or PTA (n = 143). The end points through 12 months included DUS core laboratory-adjudicated primary patency and clinically driven target lesion revascularization (CD-TLR) using Kaplan-Meier estimates and primary safety using proportions. A propensity-matched analysis of DCB (n = 466) to PTA (n = 136) was conducted to address confounders. At 12 months, DCB compared with PTA had significantly greater primary patency (88.8% vs 53.9%; P < .001), freedom from CD-TLR (94.3% vs 80.2%; P < .001), and better primary safety composite end point (94.1% vs 78.0%; P < .001). After propensity-matched analysis, DCB remained superior to PTA at 12 months for primary patency (90.5% vs 53.8%; P < .001), freedom from CD-TLR (96.9% vs 80.7%; P < .001), and the primary safety composite end point (96.3% vs 78.4%; P < .001). Across multiple prespecified subgroup analyses, including provisional stenting, DCB remained persistently superior to PTA. In the largest, DUS core laboratory-adjudicated, multiethnic, pooled DCB series to date, the IN.PACT Admiral DCB demonstrated significantly greater primary patency, freedom from CD-TLR, and better composite safety at 12 months compared with PTA.